PENENTUAN KADAR FENOLIK DAN FLAVONOID TOTAL PADA BUAH KELAPA SAWIT (Elais guineensis Jacq) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Lestari, Lestari; Ata, Putri Fritami; Yulianti, Ayu Dwi; Hasan, Hafia; Cahyo, Risky Nor; Rahman, Zainur Arif; Rahmadani, Agung; Erika, Farah (UIN AR-RANIRY, 2023)
The oil palm is a widely cultivated plant recognized by the public for its production of industrial raw materials for everyday use. Oil palm is rich in potential antioxidant activity, primarily due to its high content of phenolic and flavonoid compunds. This research aimed to assess the levels of total phenolic and flavonoid compunds in oil palm fruit. The extract sample was examined using the UV-Vis Spectrophotometry method, with the total phenolic measured at 744.8 nm, the total flavoinoid content at 440. The findigs indicated that the total phenolic content in the oil palm fruit extract was 1.46 mg/L while the total flavonoid content was 5.81 mg/L.